Hasil Pengobatan dan Variasi Biaya TB-MDR/XDR dengan Strategi PMDT di RSUP Persahabatan - Soepandi, Priyanti (UI Scholars Hub, 2014)
The treatment duration of MDR-TB patients is very long approximately, 18 until 24 months and the cost is very expensive. This study aimed to find out the treatment outcome as well as the cost variation of MDR/XDR-TB patients. This is an operational research using quantitative and qualitative mix methods. The sample were treatedMDR/XDR-TB patients who started the treatment from August 2009 until December 31, 2010. Total number of sample were 104 patients. The study revealed that the duration of treatment for XDR-TB patients is longer than MDR TB patients with lower success rate. The cost per patient of TB XDR were cured and completed treatment was USD 9,357 and USD 7,373 for the XDR-TB patients and statistically significant. The cost spent for XDR-TB patients who died during the treatment was higher compare to MDR-TB patients, USD 6,453 and USD 3,484 respectively. Additional time for length of treatment would give the probability of spending USD 11,75 per day. Male TB-MDR patients who live in East Jakarta with length of treatment less than 569 days have the curing chance 1.7 fold as compared to females TB-XDR patients with the same condition in term of length of stay.